Vibration-induced postural reactions: a scoping review on parameters and populations studied - Bertrand-Charette, Michaël; Perron, Marie-Pier; da Silva, Rubens A.; Beaulieu, Louis-David (Frontiers in Human Neuroscience, 2024)
Objective: Mechanical vibration is an effective way for externally activating Ia primary endings of the muscle spindles and skin mechanoreceptors. Despite its popularity in proprioception and postural control studies, there is still no review covering the wide variety of vibration parameters or locations used in studies. The main purpose of this scoping review was thus to give an overview of general vibration parameters and to identify, if available, the rationale for justifying methodological choices concerning vibration parameters. Methods: Three databases (Pubmed, CINHAL, SPORTDiscus) were searched from inception to July 2022. Included articles were to focus on the study of muscle spindles and skin mechanoreceptors vibration in humans and assess postural control. Following inclusion, data regarding demographic information, populations, vibration parameters and rationale were extracted and summarized. Results: 147 articles were included, mostly targeting lower extremities (n=137) and adults (n=126). The parameters used varied widely but were most often around 80Hz, at an amplitude of 1mm for 10-20 seconds. Regarding rationales, nearly 50% of the studies did not include any, whereas those including one mainly cited the same two studies, without elaborating specifically on the parameter’s choice. Conclusion: This scoping review provided a comprehensive description of the population recruited and parameters used for vibration protocols in current studies with humans. Despite many studies, there remain important gaps of knowledge that needs to be filled, especially for vibration amplitude and duration parameters in various populations.